Video-signal processing method, program of video-signal processing method, recording medium having recorded thereon program of video-signal processing method, and video-signal processing apparatus - KIMURA, SEIJI; OGATA, MASAMI (2010)
A video-signal processing method for measuring a noise level of an input video signal includes the steps of detecting an intra-field or intra-frame feature for each region that is set in the input video signal, the intra-field or intra-frame feature representing a noise level in the input video signal within a field or frame; checking the intra-field or intra-frame feature against a noise-free-region threshold, and excluding regions with which the intra-field or intra-frame feature is less than the noise-free-region threshold from subjects of noise-level measurement; and outputting a result of noise-level measurement by statistically processing the intra-field or intra-frame features of regions remaining without being excluded.